Caregivers and Babies in Interaction: A Study of Two Families in Wonosobo, Central Java - Kurniawati, Wira; Putri, Clorinda Zakiyya (Universitas PGRI Semarang, 2024)
Parentese in each community has its own characteristics. This study aims to describe the interaction between caregivers and infants with a case study in two Javanese families living in the Wonosobo urban area (mother, babysitter, grandmother, and baby aged 0;4 [K1] and 1;6 [K2]), Central Java. This research used the ethnographic method through observation involving both families. The results showed that knowledge of the competence and cognition ability of the baby became the background for caregivers to adjust themselves so as to create an asymmetrical position. This places the caregiver as the party who